Two new species of Begonia (Begoniaceae) from Bukit Tigapuluh National Park, Sumatra, Indonesia - Deden Girmansyah (BRIN Publishing (Penerbit BRIN), 2012)
Two new species of Begonia (Begoniaceae) from Bukit Tigapuluh National Park, Sumatra, Indonesia are described. Those are Begonia triginticollium Girm. belongs to Begonia section Bracteibegonia and Begonia dolichocarpa Girm. belongs to Begonia section Petermannia.